1881 Pa. Laws 111, No. 124, § 1 - (:unkn) unknown (My University, 1881)
makes any person, "who shall knowingly and willfully sell or cause to be sold, to any person under sixteen years of age, any cannon, revolver, pistol or other such deadly weapon, ... shall, in every such case, be guilty of a misdemeanor, and upon conviction thereof shall be sentenced to pay a fine not exceeding three hundred dollars."
Keywords: TRANSFER - MINORS